Rereading Management Education and Development: Drift or Thrust Into the 21st Century? (Academy of Management Review, 1990)
The article reviews the book ?Management Education & Development: Drift or Thrust Into the 21st Century?? by Lyman Porter and Lawrence McKibbin.